A surface-enhanced Raman scattering active core/shell structure based on enzyme-guided crystal growth for bisphenol A detection. Issue 31 (1st August 2018) - Xu, Zhou; Wang, Rong; Mei, Bo; Ding, Li; Wang, Libing; Chen, Maolong; Cheng, Yunhui
Abstract : Herein, a universal surface-enhanced Raman scattering (SERS) detection platform based on enzyme-guided crystal growth has been fabricated for the first time. Abstract : Herein, a universal surface-enhanced Raman scattering (SERS) detection platform based on enzyme-guided crystal growth has been fabricated for the first time. In this system, the BPA-aptamer-modified enzyme glucose oxidase was mixed with the complementary DNA sequences of the BPA-aptamer-coated AuNSs, leading to the reduction in crystallization rate to form the core/shell structure and generate the SERS signal. Because of the different concentrations of the BPA target, the crystallization degree of the AuNS surface varied which led to the corresponding SERS signals. Our results showed that this method allowed a limit of detection of 5 × 10 −17 g mL −1 for BPA. This work opens a new horizon for constructing promising SERS sensors for environmental monitoring and food safety.